Model Pembelajaran Project Based Learning Berbasis Instagram melalui Pendekatan Mobile Learning dalam Membantu Mahasiswa Memahami Tugas Akhir - Yaldi, Destri; Kurniadi, Romi (Asatiza: Jurnal Pendidikan, 2024)
M-Learning allows easier and wider access to learning. The combination of images, video, audio, and interactive interaction allows for a more engaging learning experience and allows students to be actively involved in learning. The purpose of this study is to describe the application of the steps of the Instagram-based project-based learning model with a Mobile Learning approach in helping students understand the final project. This research is classroom action research (PTK). There are two cycles in this class action research. In each cycle the learning process has improved according to the predetermined assessment aspects. Group 4 had a considerable percentage change of 22% where the first cycle score of groups 4 was 64.6 and increased in cycle II to 79. The highest scores in cycle II were in groups 1 and 5 where each percentage change was 12% in group 1 and 16% in group 5. Combining the popularity of Instagram with a project-based learning approach can help students learn research methodology courses in a practical, relevant way and allow students to learn anytime and anywhere.